Agressor sexual de crianças e adolescentes e fatores associados à violação e vítimas - Santos, Clarice Alves dos (2012)
Objectives: Characterizing sexual offenders against children and adolescents and the violation profile (sex and age), looking for possible associations between the typology of the perpetrators and those profiles, according to records of police stations and specialized civilian police (DAI, DEAM, DERCA) of Feira de Santana - Bahia. Method: cross sectional study, exploratory, based on the Survey of Police, Occurrence Bulletins and detailed terms of these instances, in the period from 2005 to 2010. Bivariate analyzes were performed through the prevalence ratio and confidence intervals, to determine possible associations between the type and characteristics of perpetrators and victims of rape. In order to assess the extent of statistical significance we used the chi-square test, adopting α = 5%. The proposal of the multivariate analysis (logistic regression) justifies further study of the bivariate associations, considering the independent variable (age of offender), the dependent variables (type of violation and characteristics of the victim) and covariates (socio-demographic characteristics, history and habits of the offender). The analysis was performed with the aid of SPSS 10.0 and R Foundation for Statistical Computing. Results: This thesis was presented in the form of article, which result suggests that most offenders were male (98.0%), single marital status (61.3%), and adult (25-49) (40%), 27,5% adolescents and 17.0% of young, about 60%, were one cycle known to the victim (neighbors / community members, friends, lovers and colleagues), 16.5% were father or stepfather and 10.5% other family members. The context of occurrence was extrafamilial (72.3%), with physical contact (88.3%), penetration (66.7%) and involving physical aggression (42.9%). The recurrence of abuse and the involvement of single offender were observed in 41.8% and 86.4% of cases, respectively. Significant associations were found between teenage offender and the occurrence of abuse outside the family context, with penetration, intimidation and physical assault / threat. The gender of the victim showed a statistical association between adolescent offender, marital status single, with a history of arrest, and participation of multiple offenders the victimization. Conclusions: the significant participation of adolescents and young in the condition of offenders, and the high prevalence of sexual abuse outside the family context, involving serious violations, perpetrated by adolescents offenders, in addition to the significant participation of molesters in the cycle of living victims (neighbors, people community, friends, colleagues, lovers and family), suggests the need for action by different social sectors in the effective prevention measures for interruption of the cycle violation - the generational transmission of aggression and violence. This phenomenon constitutes a current challenge for public policies and different areas of knowledge, requiring to investments aimed at the protection and well being of future generations, in the enjoyment of fundamental rights, guaranteed by laws, in different countries and sociocultural contexts.